PENGARUH LATIHAN BALL FEELING DAN AGILITY TERHADAP KETERAMPILAN MENGGIRING BOLA DALAM PERMAINAN SEPAK BOLA - Zaenul Ansori; Subagio; Noor Akhmad (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2023)
This study aims to determine the effect of differences in figure eight and dribble "z" pattern exercises on dribbling skills in soccer games at Club Ani Soccer Mataram. The design used in this study was an experimental research type with two-group pre-test and post-test. The population in this study were all Mataram U23 Ani soccer players in 2021, totaling 20 people. Sampling using purposive sampling technique is one of the sampling techniques in which research determines the performance of the sample by determining the specific characteristics of the age of junior players 19 to 23 years. Divided into 2 groups, 10 players in group A who practiced figue eights and group B 10 players used dribble z peterren training. The sample determination in each group is done by random (random) by drawing from the results of the dribble ability ranking which is paired with rank one with two, three with four, five with six and so on, and it is determined that the first one is taken in the figure eights exercise group and the second in Peterren's Z dribble exercise group. Data analysis using the t-test formula (t-test). The results of data analysis show that the t-count value is 11,455> t table, 1.729 with a significant level of 5%. On this basis, the null hypothesis (Ho) which reads "There is no effect of figure training and z pettren dribble on dribble skills at Club Ani Soccer Mataram in 2021", "Rejected". While the alternative hypothesis (Ha) which reads "There is an effect of figure eights and dribble z peterren t training on dribbling skills at Club Ani Socceer Mataram in 2021", "Accepted". Sehinngaaa can be concluded. Based on the results of data analysis, it can be concluded that: 1. There is an effect of figure eights training on the dribbling ability of Ani soccer Mataram club players in 2021 2. There is an effect of dribbling training on z peterren's dribbling ability in club players Ani soccer Mataram Year 2021 3. There is a difference in the effect of figure eights training with z Peter dribbling training on the dribbling ability of the Ani soccer Mataram club players in 2021.